PENYETARAAN POLA KARIER PASCA JABATAN ADMINISTRASI KE JABATAN FUNGSIONAL - Citra Permatasari; Fifi Ariani (Puslatbang KHAN, 2021)
This study was structured with the aim of looking at how career patterns of civil servant who experienced inpassing from administrative positions turned into functional positions in an organization. The existence of this inpaasing certainly has a great influence on roles and tasks that are different from the previous position at office. This research uses literature study method, a research approach that is carried out by reviewing existing literature, both from library studies and other scientific research. The results of this study will later show that career equality from administrative positions to functional positions affects the map of positions and performance in an organization. With this inpassing, it is expected that the organization will become more dynamic, agile, effective and efficient supported by professional, competitive and excellent human resources.